Islamic international law and the settlement of international disputes - Ahamat, Haniff (Institute Of Diplomacy and Foreign Relations (IDFR) Ministry of Foreign Affairs, Malaysia, 2014)
This article examines the possibility of institutionalising Islamic international law or siyar in international dispute settlement. This article starts by arguing that Islamic international law had developed as a branch of law since the 8th century but it started to decline following the colonisation of the Muslim States by the West. With the emergence of independent Muslim States however, the revival of such law is possible and this also includes the possible use in dispute settlement. This article finds that Article 38 of the ICJ Statute could provide the avenues for Islamic international law rules to be referred to by the relevant international adjudicating bodies but based on case law, the avenues are confined to general principles of law.